Perceived sexual self-control and condom use with primary and casual sex partners: age and relationship agreement differences in a Portuguese sample. Issue 10 (3rd October 2019) - Rodrigues, David L.; Prada, Marília; Lopes, Diniz
Abstract: Objective: Consistent condom use is still not ideal. Research showed that perceived sexual self-control is associated with greater likelihood of using condoms. However, this association seems to vary according to age and relationship agreement (i.e. non-consensual non-monogamy, NCNM vs. consensual non-monogamy, CNM). Design: Cross-sectional study with 307 heterosexual users of a dating web site for romantically involved individuals (81.8% men; M age = 42.24, SD = 9.65, range: 23–76 years). All individuals were in a romantic relationship ( M length = 13.47 years, SD = 9.39). Measures: Demographic information, perceived sexual self-control, condom use frequency (casual sex partners; primary partner in the last 3 months) and relationship agreement. Results: Independently of relationship agreement, perceived sexual self-control was positively associated with condom use frequency with casual sex partners among younger and middle age participants, but not older ones (>49 years). Regarding the primary partner, a similar pattern emerged for CNM participants. In contrast, no significant association between perceived sexual self-control and condom use frequency with the primary partner emerged for NCNM individuals, regardless of age. Conclusion: Our findings can inform evidence-based strategies to promote consistent condom use as an effective behaviour to prevent sexually transmitted infections, especially among older and NCNM individuals.